The Level of Proficiency in Verbal and Non-Verbal Interpersonal Communication Among Undergraduate Technology Students at FPTV, UTHM - AHMAD, MUHAMMAD HAKIM; Ali, Azita (Research and Innovation in Technical and Vocational Education and Training, 2024)
Communication represents an indispensable skill for every student. Theactive engagement of students in both verbal and non-verbalcommunication significantly influences their academic performance.Nonetheless, certain students fail to attain mastery in verbal and non-verbal communication skills, impacting their employability immediatelyafter graduation. Consequently, this study aims to identify theproficiency levels of verbal and non-verbal communication amongBachelor of Technology students at FPTV. The study adopts a surveydesign utilizing a quantitative approach, employing a questionnaire tocollect data from 252 technology undergraduate students across threecohorts. The data undergoes analysis through descriptive statisticalmethods, including mean values and standard deviation, alongside theMann-Whitney U test to discern gender-based differences. The study'sresults indicate a high level of proficiency in verbal and non-verbalcommunication among technology undergraduate students.Furthermore, the findings reveal no significant difference in the masteryof verbal and non-verbal communication based on gender. Ultimately,the majority of Bachelor of Technology students at FPTV demonstrateadeptness in both verbal and non-verbal communication. This study'simpact extends to informing future research endeavors exploring thebroader landscape of verbal and non-verbal communication mastery.